Assessing The Effects Of Polyolefin Fiber On The Properties Of Modified Asphalt Binder - Zali, urul Hidayah Mat
In recent years, the modification of asphalt binders has become popular in asphalt pavement construction. Over time, as the traffic volumes and loads increase, the asphalt binder degrades and eventually unable to resist and endure the loads, thus damaging the roads. The addition of polymer fiber reinforcement and other methods for modification of asphalt are promising research methods to overcome these problems. Therefore, a test method in determining the physical and rheological properties of modified asphalt binder and conventional binder is crucial to improve the rutting performance and elastic behavior of asphalt binder. This study investigates the effects of polyolefin on the unaged and aged polymer-modified binders. The laboratory tests considered are penetration, ductility, softening point, flash point, elastic recovery, and torsional recovery and rheological test. The 0.05% from the total weight of polymer-modified binder has been found to improve the rutting resistance and increase the viscosity of the asphalt binder, but the elastic behavior of the modified binder has insignificantly changed compared to conventional asphalt binder. Apart from that, the performance on fatigue resistance after long-term aging is reduced since the elasticity after adding polyolefin has insignificantly changes. A further study is necessary to quantify how the molecular arrangement of the polyolefin changes during the aging process since the stiffness and elasticity of modified asphalt binder is changed after short-term aging (STA). This study helps to understand the reason behind the alteration and how it effects binder stiffness in details.